Pharmacokinetics of Anthraquinones from Medicinal Plants - Wang, Dongpeng; Wang, Xian-He; Yu, Xiongjie; Cao, Fengjun; Cai, Xiaojun; Chen, Ping; Li, Minglun; Feng, Yibin; Li, Hongliang; Wang, Xuanbin (Frontiers in Pharmacology, 2021)
Anthraquinones are bioactive natural products, some of which are active components in medicinal medicines, especially Chinese medicines. These compounds exert actions including purgation, anti-inflammation, immunoregulation, antihyperlipidemia, and anticancer effects. This study aimed to review the pharmacokinetics (PKs) of anthraquinones, which are importantly associated with their pharmacological and toxicological effects. Anthraquinones are absorbed mainly in intestines. The absorption rates of free anthraquinones are faster than those of their conjugated glycosides because of the higher liposolubility. A fluctuation in blood concentration and two absorption peaks of anthraquinones may result from the hepato-intestinal circulation, reabsorption, and transformation. Anthraquinones are widely distributed throughout the body, mainly in blood-flow rich organs and tissues, such as blood, intestines, stomach, liver, lung, kidney, and fat. The metabolic pathways of anthraquinones are hydrolysis, glycuronidation, sulfation, methylation/demethylation, hydroxylation/dehydroxylation, oxidation/reduction (hydrogenation), acetylation and esterification by intestinal flora and liver metabolic enzymes, among which hydrolysis, glycuronidation and sulfation are dominant. Of note, anthraquinones can be transformed into each other. The main excretion routes for anthraquinones are the kidney, recta, and gallbladder. Conclusion: Some anthraquinones and their glycosides, such as aloe-emodin, chrysophanol, emodin, physcion, rhein and sennosides, have attracted the most PK research interest due to their more biological activities and/or detectability. Anthraquinones are mainly absorbed in the intestines and are mostly distributed in blood flow-rich tissues and organs. Transformation into another anthraquinone may increase the blood concentration of the latter, leading to an increased pharmacological and/or toxicological effect. Drug-drug interactions influencing PK may provide insights into drug compatibility theory to enhance or reduce pharmacological/toxicological effects in Chinese medicine formulae and deserve deep investigation.